Description Of Vaping Behavior on Stress Symptoms - Hutasuhut, Anissa Sabillah (Pena Cendekia Insani, 2024)
Electronic cigarettes are a technology designed to help regular cigarette consumers quit. The development of electric cigarettes in Indonesia has formed a drug regulatory agency, conducting research related to electronic cigarettes. The purpose of this study was to describe the vaping behavior of young male students towards stress symptoms. This research is a quantitative research method. This data collection technique was carried out by direct observation and survey sampling techniques using random sampling techniques. The research instrument used a questionnaire with a population or subject of 35 male adolescents. It is known that of the 35 respondents who are still teenagers, there are 6 young respondents who smoke electric or vaping and are still smoking today. Smoking becomes a daily life and binds them every day, some of them also know worry and anxiety when they can't or find it difficult to refuse vaping.